Neoplatonism and the philosophy of nature - Wilberding, James; Horn, Christoph (Oxford, U.K. Oxford University Press, 2012)
"Despite Platonism's unquestioned claim to being one of the most influential movements in the history of philosophy, for a long time the conventional wisdom was that Platonists of late antiquity, or Neoplatonists, were so focused on otherworldly metaphysics that they simply neglected any serious study of the sensible world, which after all is 'merely' an image of the intelligible world. Only recently has this conventional wisdom begun to be dispelled. In fact, it is precisely because these thinkers did see the sensible world as an image of the intelligible world that they devoted so much time and energy to understanding its inner workings. Thus we find Neoplatonists writing on embryology, physiology, meteorology, and astronomy, among other subjects. Neoplatonism and the Philosophy of Nature collects essays by leading international scholars in the field which shed new light on how the Neoplatonists sought to understand and explain nature and natural phenomena. It is thematically divided into two parts, with the first part--The General Metaphysics of Nature--directed at the explication of central Neoplatonic metaphysical doctrines and their relation to the natural world, and the second part--Platonic Approaches to Individual Sciences--showing how these same doctrines play out in individual natural sciences such as elemental physics, geography, and biology. Together these essays show that a serious examination of Neoplatonic natural philosophy has far-reaching consequences for our general understanding of the metaphysics of Platonism as well as for our evaluation of their place in the history of science."--Publisher's website.
The general metaphysics of nature: Plotinus on logos / Lloyd P. Gerson. The significance of 'physics' in Porphyry : the problem of body and matter / Andrew Smith. Self-motion and reflection : Hermias and Proclus on the harmony of Plato and Aristotle on the soul / Stephen Menn. Nature in Proclus : from irrational immanent principle to goddess / Alain Lernould. Platonism in early modern natural philosophy : the case of Leibniz and Conway / Christia Mercer -- Platonic approaches to individual sciences: Aristotelian objections and post-Aristotelian responses to Plato's elemental theory / Ian Mueller. In defence of geometric atomism : explaining elemental properties / Jan Opsomer. Plato's geography : Damascius' interpretation of the Phaedo myth / Carlos Steel. Neoplatonists on 'spontaneous' generation / James Wilberding. Aspects of biology in Plotinus / Christoph Horn.
Includes bibliographical references (pages [229]-238) and indexes.
Keywords: Neoplatonism; Philosophy of nature -- History